Diversidad polínica en el bosque siempre verde montano bajo de la cordillera occidental de los andes del Cantón la Maná Parroquia de Guasaganda sector el Malqui. - Caizapanta Guaman, Leslie Mercedes (2022)
In Ecuador, no research has been developed on the palynological topic that helps us to understand the morphological structure and propagation of the pollen grain in a natural environment as it is developed in the community of Quindigua in the "Malqui" sector located in the altitudinal floor of the Evergreen Montane Forest of the Western Cordillera of the Andes. The execution of the research project was carried out through the execution of three phases: the field, laboratory and cabinet phase with the elaboration of quantitative and qualitative lists that will allow describing the parameters of vegetal characterization, morphology of the pollen grain and its characteristics. For which a total of 92 individuals with innate characteristics were recorded, being the species with the highest Relative Density per species (RnD) the Yellow Canelo species, which represents 18.28%, For the Relative Dominance per family (DmR) we calculated the basal area of each of the families respectively, and we have the result that the Lauracea family occupies 40.99%, it is the family that predominates in the registry, in the Importance Value Index (IVI) the Lauracea family with 40.42% is the most important and the one that we found the most. There is a high diversity since it is 0. 08, the species for the determination of the pollen grain were taken outside the plot since there were no fertile species Huicundo, Cañitas, Callanayuyo, Zagalita, Capachito, Salvia lemmoni, of each of these species I determine morphologically as its symmetry, polarity, size, shape and its opening, for this research in the evergreen montane forest it is needed the flowering dates of the area to have a monitoring since it has a high diversity of species. With the present work we intend to begin research on the types of pollen that are found and study their morphology.